Enhancing CO2 absorption with amino acid ionic liquid [N1111][Gly] aqueous solution by twin-liquid film flow: Experimental and numerical study. (20th July 2022) - He, Long; Xie, Hanguang; Zong, Yuan; Zhao, Ling; Dai, Gance
Highlights: The rheological response of [N1111 ][Gly] aqueous solution during CO2 capture. Twin-liquid film behavior with [N1111 ][Gly] aqueous solution and its mass transfer performance. Film thickness is reduced and film velocity is improved for high viscosity [N1111 ][Gly] aqueous solution by twin-liquid film. Accommodation of the twin-liquid film to fluid viscosity by modulating window dimensions. Abstract: Tetramethylamine glycine ([N1111 ][Gly]) (ILs) is a potential substitute for the alcohol amine absorbent. However, its high viscosity restricts industrial CO2 absorption due to poor mass transfer performance. Surface renewal is the key to enhance interfacial mass transfer for highly viscous fluids. Considering the rheological response of the [N1111 ][Gly] aqueous solution during CO2 capture, the twin-liquid film is suggested for the [N1111 ][Gly] aqueous solution. The behavior of the twin-liquid film has been investigated by flow experiments and numerical simulation. Reduction of film thickness and improvement of surface velocity can be achieved by the interplay between the twin films, which enhances surface renewal frequency. The accommodation of the twin-liquid film to fluid viscosity can be satisfied by modulating window dimensions. The enhanced mass transfer performance of the twin-liquid film with [N1111 ][Gly] aqueous solution, illustrated by enhanced surface renewal frequency, proves it a feasible way for industrial CO2 capture.